"The Fact She Has Anorexia Fits in Perfectly": Beverley Allitt, Self-Starvation, and Media Narratives of Criminal Femininity. Issue 1 (2nd January 2021) - Holmes, Su
Abstract: This article examines the press construction in the early 1990s of Beverley Allitt, the nurse known as one of the Britain's most prolific women serial killers, focusing on Allitt's diagnosis of anorexia at the time of her trial and how it shaped understandings of her mental state, her character, and her perceived culpability. It is the relationship between Allitt, gender, and everyday constructions of anorexia that is of interest here, particularly in terms of how her image contributed to media discourses on self-starvation and femininity. The analysis suggests that Allitt's anorexia was primarily understood in terms of manipulation, inauthenticity, and performance—discourses which consolidated perniciously gendered conceptions of self-starvation, as well as the problematic clinical practices through which anorexia was "treated." As these treatment practices continue to have a legacy today, it is crucial to examine how they have been normalized and legitimized through popular media discourse.